2017
DOI: 10.1021/acscatal.7b00665
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Efficient Conversion of Methane to Aromatics by Coupling Methylation Reaction”

Abstract: Liu et al. recently reported their results on coconversion of methane and methanol at 973 K over a typical methane dehydroaromatization (MDA) catalysts, Mo/HZSM-5. 1 In this work, the authors claimed that adding a small amount of methanol to a methane feed led to more than two times higher methane conversion, substantially higher xylene and toluene selectivities (i.e., combined ca. 80%, nearly an order of magnitude increase as compared to experiments without methanol), and improved catalyst stability to such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
6
1
Order By: Relevance
“…In summary, given the complexity of the reaction network, it is believed that the performance of methane–methanol cofeed reaction is highly dependent on the process conditions (such as CH 4 /CH 3 OH ratio, inlet temperature of CH 3 OH, conditions of inlet feed, and GHSV) and catalyst properties (such as preparation method, location of Mo species, and surface acid properties). For example, the catalyst employed in the work of Kosinov and Hensen deactivated much faster than ours, indicating that the catalyst properties are quite different from ours.…”
contrasting
confidence: 71%
See 4 more Smart Citations
“…In summary, given the complexity of the reaction network, it is believed that the performance of methane–methanol cofeed reaction is highly dependent on the process conditions (such as CH 4 /CH 3 OH ratio, inlet temperature of CH 3 OH, conditions of inlet feed, and GHSV) and catalyst properties (such as preparation method, location of Mo species, and surface acid properties). For example, the catalyst employed in the work of Kosinov and Hensen deactivated much faster than ours, indicating that the catalyst properties are quite different from ours.…”
contrasting
confidence: 71%
“…This result was also obtained by Iritani et al, as 13 CO isotopic labeling tracer studies showed that more than 80% of the carbon in a benzene molecule comes from 13 CO in the CO−CH 4 cofeeding reaction over silica-supported noble-metal catalysts under atmospheric pressures. 12 These results are in disagreement with the conclusion by Kosinov and Hensen et al 2 who claimed that the selectivity of aromatics was not affected by cofeed oxygenates.…”
mentioning
confidence: 59%
See 3 more Smart Citations